Effect of mixed cropping of water yam (Dioscorea alata) on Ganoderma disease of oil palm - Fadli, Rahmad; Suwandi, Suwandi; Nurhayati, Nurhayati; Muslim, A.; Irsan, Chandra (Journal of Phytology, 2023)
Basal stem rot caused by a soil-borne fungus, Ganoderma boninense, is one of the most severe diseases in monoculture oil palm plantations. The effect of mixed cropping with water yam on infection and inoculum potential of Ganoderma boninense on oil palm seedlings was assessed under a pot experiment. Plant inoculation with rubber woodblock (RWB)-colonized Ganoderma induced disease on both mixed cropped hosts (multiple host infection), but with less severe root necrotic and less plant mortality relative to inoculation on a single oil palm host. Inoculum potential of the pathogen was reduced under mixed cropping, as shown by more considerable RWB decay than a single host, and the fungal survival was suppressed to be 55% for 12 months trial. Water yam mixed cropping did not interfere with the growth of the inoculated oil palm seedling. This study revealed the multiple host infection under mixed cropping with water yam suppressed damage caused by Ganoderma boninense to oil palm as the primary host.